SIR-Spheres® Y-90 resin microspheres in chemotherapy refractory or intolerant patients with metastatic colorectal cancer. (May 2019) - Coretti, Silvia; Rumi, Filippo; Sacchini, Dario; Cicchetti, Americo
Selective internal radiation therapy is a form of intra-arterial brachytherapy used to treat primary liver cancer and liver metastases. This article aims to provide an overview of the clinical, economic, organizational legal, social and ethical impact of selective internal radiation therapy using SIR-Spheres Y-90 resin microspheres in the treatment of patients with unresectable, liver-dominant metastatic colorectal cancer who are refractory to or intolerant of chemotherapy. A systematic literature review was performed by querying PubMed, Scopus, EBSCO, CRD and GIN. Two reviewers blindly screened the records retrieved against predefined inclusion/exclusion criteria. The selected studies where summarized following a simplified version of the EuNetHTA Core Model ® 2.1. The studies included evaluated selective internal radiation therapy in first-line or further-line treatment and showed a good safety and tolerability profile and significant improvement in efficacy expressed as time to liver progression, progression-free survival and overall survival. Selective internal radiation therapy should be provided in specialized centres and administered by a multidisciplinary team. A hub-and-spoke network could be a viable option to guarantee access to this technology across jurisdictions. The lack of a specific diagnosis-related group tariff accounting for the cost of the device could be seen as the major obstacle to a fair diffusion of this technology. The economic evaluations currently available show the cost-effectiveness of this technology in the population under study. Selective internal radiation therapy using SIR-Spheres Y-90 resin microspheres appears to be a clinically effective and cost-effective option in the treatment of metastatic colorectal cancer patients who are chemotherapy refractory or chemotherapy intolerant.